SDG6 clean water and sanitation : balancing the water cycle for sustainable life on earth - Kremere, Eva; Morgan, Edward; Obani, Pedi (Bingley, U.K. : Emerald Publishing Limited, 2019)
Bridging academic discussion and real-world case studies, this book considers the challenge, posed by SDG6, of balancing the provision of the basic human right of access to water whilst not eroding our capacity to live sustainably in a rapidly changing world.
Includes bibliographical references and index.
Print version record.
Keywords: Water-supply -- Health aspects; Drinking water -- Health aspects; Water cycles; Health & Fitness -- Health Care Issues; Water purification & desalinization